An Analysis of Recount Text Comprehension At the Eighth Grade of SMPN 12 Jambi City - Yenti Yenti (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
In Junior High School, the students should have reading skill. Good achievement in reading is very important for the students. When the researcher did observation at the eighth grade students of SMPN 12 Jambi City, it was found that some of the students have difficulties in comprehending a recount text. The aim of this research is to find out students difficulties in comprehending a recount text at the eighth grade students of SMPN 12 Jambi City Academic Year 2018/2019. The researcher used qualitative method to analyze the data. There were thirty two students of the eighth year of SMPN 12 participated in this research. Observation, questionnaire and interview data were collected, analyzed and collated. The researcher found that some students had difficulty in understanding the content of the text and difficult to interpret the English language, which is almost the same answer choices that confuse students. Students simply read without understanding the text, not thorough in answering questions. The students difficult in comprehending a recount text questions. There are inability to access the content of the text.